Current Perspective of Diagnostic and Treatment of Rabies: A Literature Review - Pratama, Nauval Lazuardi; Rahmadinie, Amalia (Journal of Diverse Medical Research : Medicosphere, 2024)
Background. Rabies is a zoonotic disease caused by the rabies virus (RABV) from the Lyssavirus genus. Transmitted through saliva, typically via bites or scratches, it causes fatal neurological disorders if untreated. Annually, rabies claims 59,000 lives, with most cases in rural Africa and Asia, where dogs are the primary reservoirs. Despite available vaccines, low coverage in resource-limited settings makes rabies a persistent public health issue. Effective prevention requires vaccination programs, public awareness, and animal population control. Methods. This study was conducted through a literature review using PubMed and Google Scholar as primary sources. Relevant peer-reviewed articles and research papers on rabies epidemiology, clinical features, pathophysiology, and management published in the last five years (2019–2024) were selected. Keywords such as "rabies," "Lyssavirus," and "vaccination" guided the search. Discussion. Rabies is a deadly disease with a high fatality rate once symptoms appear, making prevention through vaccination critical. Early post-exposure treatment, such as wound cleaning and immunoglobulin administration, reduces infection risks. Despite advancements in diagnostics and cost-effective vaccination methods, challenges remain in controlling rabies transmission, particularly from dogs and bats. Public awareness, improved vaccine access, and effective animal control are essential to eliminating rabies. Conclusion. Rabies is a fatal zoonotic disease with almost no chance of survival once symptoms appear. Prevention through vaccination and post-exposure treatment, including wound cleaning and immunoglobulins, is crucial. Efforts to control rabies require increased vaccination coverage, public education, and better management of animal reservoirs, especially dogs.